Effect of leunca (Solanum nigrum) on inflammatory status in rats induced by high-fat and high-sucrose diet - Gunawan, Sekar Ayu Putri; Muis, Siti Fatimah; Anjani, Gemala; Noer, Etika Ratna; Ayustaningwarno, Fitriyono (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2025)
Background: Consumption of foods that are high in calories over a long period of time is a cause of obesity and can increase proinflammatory cytokines. Leunca fruit contains various phytochemicals that act as anti-inflammatory, antioxidant, and antiobesity but not many people utilize leunca fruit as daily food.Objective: To analyze the effect of leunca fruit on TNF-α and IL-6 levels in rats induced by high fat and sucrose diet (HFSD).Methods: The research design was Randomized Post Test Only Control Group Design. The sample was 30 male Sparague Dawley rats and divided into 5 groups, namely group K1 which was given standard feed, group K2 which was induced by HFSD, group P1 which was induced by HFSD and leunca 0.8g/200gBW, group P2 which was induced by HFSD and leunca 1.6g/200gBW, and group P3 which was induced by HFSD and leunca 2.4g/200gBW. The research was conducted at the Nutrition Laboratory of the Center for Food and Nutrition Studies of Gadjah Mada University (PSPG PAU UGM) Yogyakarta in January-March 2024. Testing TNF-α and IL-6 levels through rat blood serum using the ELISA method. Data were analyzed by ANOVA and Post Hoc test.Results: There was a significant difference in TNF-α and IL-6 levels between experimental groups (p=0.00). The levels of TNF-α and IL-6 in the P1, P2, and P3 groups that received HFSD + leunca were lower than in the K2 group that received HFSD only.Conclusion: Leunca fruit can reduce proinflammatory cytokine levels (TNF-α and IL-6) in HFSD-induced rats.